Mantle structure beneath the Macaronesian volcanic islands (Cape Verde, Canaries, Madeira and Azores): A review and future directions - Civiero, Chiara; Carvalho, Joana; Silveira, Graça (Frontiers in Earth Science, 2023)
Ocean island volcanism provides a unique window into the nature of mantle composition, dynamics and evolution. The four Macaronesian archipelagos –Cape Verde, the Canaries, Madeira and the Azores– are the main magmatic systems of the Central-East Atlantic Ocean with volcanic activity that in some islands poses significant risk for the population. The recent development of regional seismic networks in these settings has provided an important step forward in mapping the underlying mantle. However, difficulties in resolving the small-scale structure with geophysical techniques persist leading to discrepancies in the interpretation of the mechanisms responsible for volcanism. Here we review results from a number of studies on the seismic mantle structure beneath the Macaronesian archipelagos including seismic tomography, receiver functions, precursors and shear-wave splitting. Several regional models show low-velocity features in the asthenosphere, a relatively thinned transition zone and complex anisotropic patterns and attribute the volcanism to mantle plumes. This inference is supported by whole-mantle tomography models, which find broad low-velocity anomalies in the lower mantle below the Central-East Atlantic. Other models call for alternative mechanisms associated with shallower mantle upwellings and purely plate tectonism. Thus, there is still no generally accepted mechanism that explains volcanism in the Macaronesia region. Future research requires improvements in the resolving power of seismic techniques to better illuminate the velocity structure at a much higher resolution than the currently achieved and ultimately define the mechanisms controlling the ocean island volcanism.